Analysis of Human Resource Management in Improving Teachers’ Competence in Early Childhood Teaching at Schools - Nazaruddin Malik; Endang Fatmawati; Ridwin Purba; Tukiyo Tukiyo; Marto Silalahi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to explain several implementations of Human Resource Management to improve the competence of early childhood education teachers, namely: human resource planning, training and human resource development. The research method uses a qualitative descriptive approach. Data collection techniques were carried out by observation, interviews and documentation taken from teachers and headmaster. Post-data collection analysis used a data reduction pattern, data display, and data verification. The main points of the research results are: (1) the human resource planning system is carried out by analyzing all activities or workloads that must be carried out by all school components. (2) human resource training and development carried out still tends to be a formality limited to success whether or not the training was implemented, and not yet oriented to the effects of the post-training that was carried out, it was able to change for the better or not the behavior and performance of the participants towards organizational goals